Urban Regeneration Practices in Developing Countries: The Case of Libreville, Gabon - Ravel N.g. Edzang; Ayşe Dilek Darby (Journal of Technology in Architecture Design and Planning)
Since the 1990s, urban regeneration projects have become important intervention mechanisms in European and American cities. They deal with improving urban areas which are decaying as a result of physical and social problems and disinvestment. In the past four decades, the consequences of these urban regeneration projects have been closely studied and their limitations have been made public by academics publishing their studies throughout the world. These studies have revealed that in order to initiate successful urban regeneration projects, rather than top-down implementations, more inclusive and participatory projects should be implemented. It is also acknowledged as an important fact that tourism-led urban regeneration projects should incorporate the themes of authenticity and local culture by including the local community and their actors in the process. While most of the documented research has focused on the developed countries’ experiences, there are relatively few studies which examine the case studies in the developing countries of the African continent. In the case of Libreville in Gabon, urban regeneration which incorporates urban tourism and authenticity appears to be one of the solutions that will allow the local community to both manage finances and structurally improve urban spaces and structures. Therefore, the present study analyses the King’s Bay waterfront regeneration project in Libreville, completed in August 2022, with reference to public participation and authenticity via online surveys which were conducted with the local community. A total of 1,009 surveys were answered by the locals, with the results revealing that despite the huge literature produced by scholars in other parts of the world, in the more singular King’s Bay urban regeneration project authoritarian and top-down approaches of the local authorities were observed by ignoring the local community’s views with reference to public participation. Accordingly, this article discusses the consequences of this approach by disclosing the survey results.